Curator's Responsibility for Errors in the Administration of Bankrupt Estate that Causes Losses to Creditors - Sri Warjiyati; Nazhif Ali Murtadho; Natasya Vernanda Putri Salsabila (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
This research discusses the Curator's responsibility in managing and settling the assets of a bankrupt debtor, especially when the Curator's negligence causes losses to creditors. Bankruptcy is often the last resort for companies facing financial difficulties. Based on Law no. 37 of 2004, the Curator has the authority to manage and settle bankruptcy assets under the supervision of a judge. However, the crucial role of the Curator also raises the risk of abuse of authority which is detrimental to creditors. This research uses normative legal methods with deductive analysis techniques, examining legal aspects related to the Curator's responsibilities, namely Law no. 37/2004 as well as accountability mechanisms if negligence or errors occur in the bankruptcy process. The research results show that the Curator can be held accountable both legally and personally if his negligence or error results in losses for creditors, with a reporting mechanism to the supervising judge as the first step. These findings highlight the importance of the Curator's integrity and professionalism to ensure fair and effective bankruptcy implementation, as well as protecting creditor rights from potential losses